Comprehensive Assessment Of An Individualized Exercise And Behavior Modification Program For Chronic Disease Patients: 2383...American College of Sports Medicine (ACSM) Annual Meeting, May 27-30, 2025, Atlanta, Georgia. - Kolar-Doornek, Melissa B.; Brown, Jessica M.; Shackelford, Daniel Y. K. (Medicine & Science in Sports & Exercise)
The article focuses on evaluating the effectiveness of a 12-week individualized exercise and behavior modification program for individuals with chronic diseases, including cardiovascular, respiratory, and type 2 diabetes. The program aimed to improve various physical health metrics, including cardiovascular fitness, muscular strength, balance, and flexibility. Results from 121 participants indicated significant improvements in multiple areas, such as peak oxygen consumption, blood pressure, strength-to-weight ratios, and overall quality of life. The findings suggest that such integrative exercise interventions can effectively address the challenges posed by chronic conditions, enhancing both physical and functional health.